Educational Strategy in Preventing HIV/AIDS: Analysis of Social, Cultural, and Digital Media Influence - Yastutik, Iryani Yuni; Setyowati, Risha (The Journal of Educational Development, 2024)
The research investigated the influence of digital media integration and social and cultural factors on the knowledge, attitudes, and preventative behaviors regarding HIV/AIDS among adolescents. The objective was to assess how these variables correlate and contribute to enhancing HIV/AIDS prevention strategies within this demographic. Utilizing a quantitative research methodology, data were collected from 398 respondents and analyzed through descriptive statistics, correlation analysis, independent samples T-tests, ANOVA, linear regression, principal component analysis (PCA), and exploratory factor analysis (EFA). The findings revealed no significant correlations between the use of digital media, social and cultural factors, and adolescents' knowledge, attitudes, and behaviors related to HIV/AIDS prevention. Similarly, regression models indicated that these variables did not significantly predict knowledge about HIV/AIDS. The PCA and EFA did not identify significant components or factors that could explain variance in responses concerning HIV/AIDS prevention. In conclusion, the study suggests that digital media, alongside social and cultural factors, does not significantly impact adolescents' knowledge, attitudes, and preventative behaviors toward HIV/AIDS. This research contributes to the scientific understanding of HIV/AIDS prevention in adolescents, indicating a need for exploring additional factors that might influence effective prevention strategies.